2015
DOI: 10.5935/1984-2295.20150053
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of Thermal Diffusivity and Heat Flow of a Soil in Agreste Pernambucano

Abstract: Conhecer as características térmicas do solo é de fundamental importância para entendimento de seus processos físicos. Este trabalho objetivou estimar o fluxo de calor do solo através da lei de Fourier para o transporte de calor e a difusividade térmica do solo utilizando seis métodos (fase, amplitude, logaritmo, condução-convecção, arco tangente e diferenças finitas) em um solo do agreste Pernambucano. Para isto, foram medidas temperaturas nas profundidades de 0,02; 0,08; 0,10; 0,20; 0,30; 0,40; 0,50 m por me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Soares et al (2014) compared six (6) methodologies to determine the diffusivity, where the conduction-convection method presented good results. In a study by Oliveira et al (2015), this algorithm more accurately represented the temperature profile before the others, for soil types similar to the one studied in this study.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…Soares et al (2014) compared six (6) methodologies to determine the diffusivity, where the conduction-convection method presented good results. In a study by Oliveira et al (2015), this algorithm more accurately represented the temperature profile before the others, for soil types similar to the one studied in this study.…”
Section: Resultsmentioning
confidence: 90%
“…The indicators showed that the simulations were very close to the one analyzed in the field. In comparison with the study carried out by Oliveira et al (2015), it is possible to observe the evolution of the simulations, when the thermal diffusivity of each layer is taken into account, and the method used has performed better than the others.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations